Diagnosis Of Nasopharyngeal Carcinoma By DNA Amplification Of EBV Genomes In Nasopharyngeal Biopsy And Fine Needle Aspiration Of Neck Nodes. - Hassan, Shahid; Yap, Y.Y; M., Ravichandran (2004)
Naspharyngeal carcinoma(NPC) is common in Malaysia but diagnosis is sometimes delayed for non-representative biopsy,submucosal disease and occult primaries - increasing morbidity and mortality. Epstein-Barr virus (EBV) is associated with all types of NPC and DNA in tumor cells is detectable by polymerase shain reaction (PCR). EBV products EBNA1,EBNA2, and LAMP1 are implicated in oncogenesis and is detectable in nodal tissue. However no similar study has been done in SOutheast-Asia with adequate sample......